Engaging Malaysia: Greening Postcolonial Memories in The Garden of Evening Mists - Ahmed Mohsen, Hamoud Yahya; Mohd Mydin, Raihanah; Othamn, Wan Mazlini (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2023)
The Garden of Evening Mists is a symbolically charged historical narrative about the ramifications of Japanese colonisation in Malaya in the 1940s. A prominent metaphor in this novel is ‘the garden’ in memorium of the protagonist’s deceased sister. This article explores the greening of postcolonial memories of the Japanese colonisation of Malaya in the novel and its deep engagement of Malaysian framed within the social, political and historical contexts. Using postcolonial ecocriticism as a reading lens, the analysis is carried out to be emblematically functional across the limitations of space and time in the country’s colonial history. The analysis displays that the author, Tan Twan Eng, through his authorial-defined social reality, re-enacts numerous snapshots from the Malaysia ecosystem in order to achieve a coherent engagement of Malaysia pre, during and post Japanese occupation. The finding also reveals that while Tan’s narrative provides us with some insights into the ways in which the Malaysians navigate various colonial and postcolonial consequences, it should also be recognized that the ecology of the land adds to the narrative. Through the intersection of the Malaysian landscape and the country’s historical context, the current article reveal how postcolonial ecocriticism is instrumental in understanding the literary canon of Malaysia.